Indigenization of Thesis Acknowledgement in English as a Foreign Language in Indonesia - Agustninus Ngadiman (Magister Scientiae, 2011)
This study is an attempt of investigating the rhetoric of thesis acknowledgement by English Department Students. Data of this study are composed of 200 students’ thesis acknowledgements written over a period of ten years (1997-2007). The Thesis acknowledgements (TAs) were collected solely from the English Department of Widya Mandala Chatolic University. The study shows that the students’ TAs (a) are colored with various kinds of formulaic expression, Grice’s maxim flouting, and parallel syntactic construction, (2) employ Hierarchical Pattern of gratitude expression, and circular or repetitive patterns of thought.